Children with bilateral cerebral palsy use their hip joint to complete a step-up task - Goyal, Vatsala; Gordon, Keith E.; Sukal-Moulton, Theresa (Frontiers in Human Neuroscience, 2024)
Performance in stair-climbing is largely associated with disruptions to mobility and community participation in children with cerebral palsy (CP). It is important to understand the nature of motor impairments responsible for making stairs a challenge in children with bilateral CP to clarify underlying causes of impaired mobility. In pediatric clinical populations, sensitive measurements of movement quality can be captured during the initial step of stair ascent. Thus, the purpose of this study was to quantify the lower limb joint moments of children with bilateral CP during the stance phases of a step-up task. Participants performed multiple stepping trials in a university gait laboratory. Outcome measures included extensor support moments (the sum of hip, knee, and ankle sagittal plane moments), hip abduction moments, and their timing. We recruited seven participants per group. We found that peak support and hip abduction moments were similar in the bilateral CP group compared to the typical development (TD) group. We also found that children with bilateral CP timed their peak moments closer together and increasingly depended on the hip joint to complete the task, especially in their more affected (MA) lower limb. Our investigation highlights some underlying causes that may make stair Deleted: Young people Deleted: extensor climbing a challenge for the CP population, including a loss of selective voluntary motor control (SVMC), and provides a possible treatment approach to strengthen lower limb muscles.